High refractive index monofunctional monomers as promising diluents for dental composites. Issue 2 (February 2021) - Catel, Yohann; Angermann, Jörg; Fässler, Pascal; Fischer, Urs; Schnur, Thomas; Moszner, Norbert
Highlights: Three aromatic monofunctional methacrylates are evaluated as high refractive index diluents for the formulation of radiopaque bulk-fill composites. Photopolymerization kinetics of these monomers are investigated by photo-DSC. Bulk-fill composites based on the new diluent monomers exhibit improved mechanical properties, reduced shrinkage force and lower water sorption in comparison with a reference composite containing TEGDMA. Abstract: Objectives: To evaluate high refractive index methacrylates as diluents for the formulation of radiopaque esthetic bulk-fill composites. Methods: 2-(4-Cumylphenoxy)ethyl methacrylate 1, 2-(2-phenylphenoxy)ethyl methacrylate 2 and 2-[2-(2-phenylphenoxy)ethoxy]ethyl methacrylate 3 were synthesized and characterized by 1 H NMR spectroscopy. The reactivity of each monomer was studied using photo-DSC. Bulk-fill composites based on monomers 1–3 were formulated. Translucency (before and after light cure) was measured using a spectrophotometer. The depth of cure and the water sorption of these materials were determined according to ISO 4049. The flexural strength and modulus of elasticity were measured using a three-point bending setup, according to ISO 4049. The shrinkage force was assessed based on a method described by Watts et al. using a universal testing machine. Results: Monomers 1–3 were easily synthesized in two steps. They exhibit a low viscosity and a high refractive index (1.553–1.573). Monofunctional methacrylates 1–3 were found to be more reactive than triethylene glycol dimethacrylate (TEGDMA). Bulk-fill composites based on these monomers were successfully prepared. They exhibit a high depth of cure and excellent esthetic properties (low transparency). These composites provide higher flexural modulus as well as lower water sorption than a corresponding material based on TEGDMA. Methacrylates 1 and 3 are particularly interesting as they led to composites showing lower shrinkage force. Significance: Methacrylates 1–3 are promising diluents for the formulation of highly esthetic radiopaque bulk-fill composites.